Clinical and laboratory aspects of vitamin D in relation to type 2 diabetes and osteoporosis. Results from the Tromsø Study and two randomized controlled trials. - Grimnes, Guri (University of Tromsø, 2011)
The papers of this thesis are not available in Munin: 1. Grimnes G, Almaas B, Eggen AE, Emaus N, Figenschau Y, Hopstock L, Hutchinson MS, Methlie P, Mihailova A, Sneve M, Torjesen P, Wilsgaard T and Jorde R.: 'Effect of smoking on the serum levels of 25-hydroxyvitamin D depends on the assay employed', European Journal of Endocrinology (2010) 163:339-48. Available at http://dx.doi.org/10.1530/EJE-10-0150 2. Grimnes G, Emaus N, Joakimsen RM, Figenschau Y, Jenssen T, Njølstad I, Schirmer H, Jorde R.: 'Baseline serum 25-hydroxyvitamin D concentrations in the Tromsø Study 1994-95 and risk of developing type 2 diabetes mellitus during eleven years of followup', Diabetic Medicine (2010);27:1107-15. Available at http://dx.doi.org/10.1111/j.1464-5491.2010.03092.x 3. Grimnes G, Figenschau Y, Almås, B, Jorde R.: 'Vitamin D, insulin secretion, sensitivity and lipids – the results from a case-control study and a randomized controlled trial using hyperglycemic clamp technique', Diabetes (2011) vol. 25, pp 1-10. Available at http://dx.doi.org/10.2337/db11-0650 4. Grimnes G, Joakimsen RM, Figenschau Y, Torjesen P, Almås B, Jorde R.: 'The effect of high dose vitamin D on bone mineral density and bone turnover markers in postmenopausal women with low bone mass – a randomized controlled one-year trial', Osteoporosis International (2012) vol. 23(1) pp. 201-211. Available at http://dx.doi.org/10.1007/s00198-011-1845-1 There has been a large interest in possible beneficial health effects of increasing the vitamin D (as measured by 25-hydroxyvitamin D (25(OH)D)) levels in the population. Data from the Tromsø Study were used to assess the relation between serum 25(OH)D levels and the risk of subsequent type 2 diabetes in 6119 participants. This risk was approximately doubled in the lowest serum 25(OH)D quartile as compared to the highest quartile. This could to a large extent be explained by higher body mass index in the lowest quartile. When thereafter comparing 52 persons with high and 108 persons with low serum 25(OH)D levels, we ...